ANALISIS RESEPSI KHALAYAK TERHADAP ISI PESAN IKLAN “DON’T KNOW KASIH NO” DALAM MEMAHAMI FENOMENA PHISING - Armansyah, Adhira Aurelia; Anam Miftakhul Huda (The Commercium, 2025)
Phishing is one of weak internet security as a service provider for ease and speed of information in the digital era. Cybercrime of phishing has occurred the banking industry in Indonesia since 2022. This study analyses the audience's reception of the advertisement "Don't Know? Kasih No!" by BCA. Using Stuart Hall's reception theory, this study explores how the audience interprets anti-phishing campaign message conveyed. The research method used is descriptive qualitative, with data collection techniques through in-depth interviews with seven informants who are BCA customers and have watched the advertisement. The study results showed that four informants were in the dominant-hegemonic position, three informants were in the negotiated position, and no informants were found in the opposition category. This study concludes that each informant has diverse views and understandings of the phishing phenomenon due to differences in background experience, education, environment, and how they think and socialize. This study recommends that the public get involved and contribute to disseminating the Anti-Phishing campaign as a form of taking a role in protecting each other and avoiding fraud.